Indian consensus statement on the management of metastatic colorectal cancer - Vaid, Ashok K.; Mohapatra, Prabrajya N.; Desai, Chirag (International Journal of Advances in Medicine, 2021)
In India, the annual incidence rates for colon cancer are 4.4 (males) and 3.9 (females) per 100,000. A common guideline for the management of metastatic colorectal cancer (mCRC) in the Indian subcontinent is lacking. Four virtual advisory board meetings consisting of a panel of 31 experts were conducted to discuss and arrive at a consensus on the treatment patterns and clinical evidence on the management of mCRC in Indian patients. The consensus covered the entirety of treatment patterns suited for the Indian subcontinent and its alignment with Pan-Asian adapted European Society for Medical Oncology guidelines. Recommendations were provided for choosing the first- and second-line agents for treatment. Types of, recommendations for, and management using salvage therapy and immunotherapy as well as management of adverse effects were discussed. Thus, the mCRC consensus is expected to serve as effective and readily available guidance for practicing oncologists across India.